A preliminary study on the effects of stingless bee honey (SBH) on fasting blood glucose in streptozotocin (STZ)-induced diabetic rat models - Anis Farihan Ismail,; Suriati Mohd Nasir,; Tuan Salwani Tuan Ismail,; Wan Amir Nizam Wan Ahmad,; Wan Faiziah Wan Abdul Rahman,; Kuttulebbai Nainamohammed Salam Sirajudeen,; Tengku Ahmad Damitri Al- Astani Tengku Din, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Diabetes is a metabolic disorder characterized by hyperglycemia due to defects in insulin secretion, insulin action, or both. SBH has good antihyperglycemic potential and has traditionally been used as an alternative treatment for diabetes mellitus (DM). Since the role of SBH in glucose control is still unclear in animal and human studies, the present study was designed to evaluate the antihyperglycemic effects of SBH in streptozotocin-induced diabetic rat models. Fifteen Sprague-Dawley rats (200-250 g) were equally divided into five groups, the first group being a normal (non-diabetic) rat and the other four groups being diabetic. The normal and untreated diabetic groups received normal saline while the other diabetic groups were treated with SBH (2 g/kg body weight), metformin (MET /250 mg/kg body weight) and SBH + MET respectively. The treatment was given within 12 days. Fasting blood glucose (FBG) was measured at baseline and every two weeks thereafter. On days 7 and 12, SBH significantly lowered FBG, comparable to the normal group (p<0.05). In the group treated with MET and the combination of SBH-MET, FBG improved only on the 12th day of treatment (p<0.05). The results show that a single SBH treatment is effective in lowering blood glucose levels. Thus, SBH could be of great value in the treatment of diabetes in humans.